Dust and Fire Explosion in Malaysia : A Review - Badhrulhisham, Abdul Aziz; Siti Ilyani, Rani; Jolius, Gimbun (2014)
Dust are fine solid airborne particles which capable to passing a standard sieve. The National Fire Protection Association (NFPA) defines dust as any finely divided solid, 420 μm or less in diameter that passed through a U.S. No 40 standard sieve (Amyotte and Eckhoff, 2010). According to British Standard Institute code BS2955:1958, dust are particles less than 76 μm in diameter (Abbasi and Abbasi, 2007).